PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN HARGA TERHADAP KEPUASAN IMPORTIR ASIACOMMERCE - Zafitri, Berliana Fira (Media Akuntansi dan Perpajakan Indonesia, 2021)
The purpose of this research is to find out the effect of service quality, trust and price on importer satisfaction at AsiaCommerce freight forwarding company. The population of this research is a clients or members of AsiaCommerce who had made import transactions and the sampling technique used non-probability sampling with a purposive sampling method. The number of samples in this research were 45 clients or members of AsiaCommerce. Data collection by the distribution of questionnaires. The data analysis method used in this research is a multiple linear regression analysis. The results of this research indicate that service quality does not have a significant effect on AsiaCommerce importer satisfaction, but trust and price have a significant effect on AsiaCommerce importer satisfaction.